N-Terminal pro-brain natriuretic peptide is a useful prognostic marker in patients with pre-capillary pulmonary hypertension and renal insufficiency - Harbaum, Lars; Hennigs, Jan K.; Baumann, Hans J.; Lüneburg, Nicole; Griesch, Elisabeth; Bokemeyer, Carsten; Grünig, Ekkehard; Klose, Hans (PLOS ONE, 2014)
N-terminal pro-brain natriuretic peptide (NT-proBNP) is a routinely used prognostic parameter in patients with pre-capillary pulmonary hypertension (PH). As it accumulates in the presence of impaired renal function, the clinical utility of NT-proBNP in PH patients with concomitant renal insufficiency remains unclear.
Gesehen am 25.09.2020